UJI AKTIVITAS ANTI JAMUR EKSTRAK MINYAK KAYU SINDUR (Sindora wallichi Benth) TERHADAP PERTUMBUHAN JAMUR Schizophyllum commune Fries - Sudarmadi, Bujang; Diba, Farah; Yanti, Hikma (JURNAL HUTAN LESTARI, 2013)
The research objective was to determine the antifungal activity and the effective concentration of extract sindur wood oil in inhibiting Schizophyllum commune Fries fungus growth. Concentration of extract sindur wood oil used for the treatment were 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14% and 16%. The toxicity testing had done by method using PDA medium mixed with the extract sindur oil. Extract sindur wood oil activity is inclusive of category for concentration 2%, strongth for concentration 4%, 6%, 8% and very strong for concentration 10%, 12%, 16%.The concentration of 16% is very strong anti-fungal activity which inhibit 100% of growth of S. commune fungi. Concentration 10% of extract wood sindur oil is optimum contration to inhibit S. commune fungus growth. Key word : Schizophyllum commune Fries, sindur wood oil, antifungal.